INFLUENCE OF PERCEIVED VALUE ON THE RELATIONSHIP BETWEEN CONSUMER NATIONAL ETHNOCENTRISM AND WILLINGNESS TO BUY COMMERCIAL BANKING SERVICES IN KENYA - Maina, S. M; Kibera, F. N.; Munyoki, J. M (European Scientific Journal, ESJ, 2015)
International marketing researchers have concentrated on establishing the influence of consumer national ethnocentrism on willingness to buy domestic products/services as opposed to foreign products/services. The purpose of this paper was to determine the mediating role of consumer perceived value on the relationship between consumer ethnocentrism and the willingness to buy banking services in Kenya. A descriptive research design which was cross sectional in nature was used in the study. Data were gathered from 374 University Staff and Students in Kenya. Data analysis was done using binary logit regression. As a multi faceted construct, consumer national ethnocentrism was found to have a negative influence on the willingness to buy banking services from foreign owned banks. These related well with other previous literature. The relationship was however mediated by several factors. Consumer perceived value was found to have a partial mediation. Findings of the study implies that foreign investors in the banking industry should have pertinent localization strategies incorporated in their broad corporate strategies to guide them not only in repositioning their products in the domestic markets but also in adapting their operations so as to enhance domestic consumption.